Supporting and engaging isolated language learners in Open and Distance Learning (ODL) classes a comparative study between a Malaysian and an Indonesian university undergraduate students / Norhaiyati Abdul Muin - Abdul Muin, Norhaiyati (2021)
Covid-19 has suddenly shifted physical classrooms to fully online. Not only educators, but also students are forced to resort to fully Open and Distance Learning (ODL) classes overnight. With lack of preparation, there are multitude of problems faced by both. Initially, the students welcomed the ability of studying at the comfort of their homes; later however, many have complained on difficulties faced in coping with ODL classes. At the same time, in changing the modes, a one-size-fits-all approach is often employed by the lecturers. In other words, internal content is converted into a form that they believe suitable for an external delivery. However, there is a significant problem with this approach, especially with students who feel isolated and disengaged from the physical classrooms. When compared to their counterparts who are more self-regulated learners, these students often face some barriers that they may not experience in face-to-face or blended learning environment to fully participate in their coursework. The online environment also poses challenges for many academic staff who need to master technological competency and proficiency within a limited time period. This paper provides one lecturer's findings and perspectives facilitating students learning online. Primary data collected from a self-administered online survey questionnaire are analysed descriptively in a general survey of trends, involving 162 survey respondents among degree students from UiTM Kelantan and an Indonesian university. It also includes students' responses and critical commentaries on some of the challenges faced by the students and the implications of more ODL classes in future